The influence of farming systems on the incidence of Aspergillus carbonarius in viticultural products - Kontaxakis, Emmanouil A. (Cranfield University, 2013)
In viticulture, the most effective way to prevent or reduce the ochratoxin A (OTA) contamination of viticultural products is the control of ochratoxigenic fungal species, and especially Aspergillus carbonarius, the predominant produce of ochratoxin A in these products. In the present study, conducted in the years 2010, 2011 and 2012, in Heraklion Prefecture (Crete, Greece), the influence of the different farming systems that are applied in the Cretan vineyards, on the incidence of A. carbonarius in grapes and soil, and hence the potential of OTA contamination of viticultural products, were examined. The impact of different cultivar characteristics, cultivation techniques (trellis system, nutrition and irrigation management, fungicides treatments) and area of cultivation was also investigated. Cont/d.